Vamos JUNTOS: Immigrants’ Organization Asserting Power Through Adult Learning? - Rola Tarek Mohamed (Adult Education Research Conference, 2023)
Through the textual analysis of the curriculum of ICE Out of PA campaign, this roundtable explores politicization processes of adult learners in an immigrants' rights organization in Philadelphia, PA.
Keywords: politicization; social movement learning; migrants' rights; textual analysis